O discurso expositivo de um espaço amazônico de educação não formal em ciência e tecnologia: o caso do Bosque da Ciência - Santos , Saulo Cezar Seiffert (2020)
the Amazon, they stand out as a link between the school and the Amazonian identity elements conveyed by ideological signs and ideologies. In this way, we conducted a research in a Science and Technology Space - STS, Science Forest of the National Institute of Research in the Amazon - NIRA, which conducts research and makes public visitation spaces available for scientific-environmental dissemination of its studies and important topics. for the region. Our objective was to understand the ideological conception of ED in the dissemination of Amazonian themes in Science and Technology of the Forest from the documents guiding the space and the collaborators (servers and monitors), when analyzing the architectural discursive construction of that space. Through a qualitative approach, we structured the investigation using the Dialogic Discourse Analysis based on the Bakhtin Circle and on the interface of the sensitive and intelligible perception of STS, in dialogue with other theorists. The information was constructed through the collection of documents and guided interviews, and we developed a proposal for the interpretation of ED mediated by narratives in three movements: a) documentary narratives - spheres: social (creation of Science Forest), - scientific (production of research), - leisure (scientific-environmental entertainment for visitors), and - communication and information (signs and banners present on the public sidewalk); b) employee narratives, namely, seven civil servants (technicians, scholarship holders and researchers from the institution) and four monitors; c) ED narrative in an exhibition, in which the Aquatic Mammals season was selected. The narratives pointed to a history of neglect for scientific institutions in Amazonas, and the creation of Bosque as a form of dialogue with popular people to learn about NIRA's work. It was noticed that the servers start from an extensionist ideology in which information and some research are available, but there is not necessarily a permanent dialogue with laboratories and researchers. The training process of the monitors was an introductory course; however, it was short and insufficient, however, enough to present the space in which the biotic, sensitive and aesthetic aspect of the attractions stand out. The vision of ideological values present was the conservationist with a biological focus (ecocentric), without dialogue with other views, tending to an authoritarian and monological discourse. The present ED is linked to the object, the manatee, for example, in an alterity relationship with the visitor, takes it as a hermeneutic experience to guide the interpretation of the plates with the intention of conservation. The ED is focused on either the monitor or the free ride, on the interaction of the object and the interpretative media with the scientific-environmental educational intention. We highlight the relevance of space discourse as an aspect that impacts the learning project.